Preclinical study of gastroprotective action of cryopreserved placenta extract - Кошурба, І.В.; Гладких, Ф.В. (My University, 2022)
Treatment and prevention of peptic ulcer of the stomach is not only medical but also social problem. As a potential gastroprotective agent, our attention was drawn to the cryopreserved extract of placenta (CEP), because the literature convincingly demonstrated that this cryoextract eliminates the ulcerogenic action of non-steroidal anti-inflammatory drugs, which has a mechanism similar to peptic ulcer disease. The aim is to conduct a comparative assessment of the severity of antiulcer activity of CEP in prophylactic, therapeutic and therapeutic-prophylactic regimens for use in the model of ethanol-prednisolone gastric lesions. Materials and methods of research. Studies were performed on laboratory male rats. To simulate damage to the gastric mucosa, rats were administered a single ethanol-prednisolone mixture: prednisolone (20 mg/kg) dissolved in 80.0% ethyl alcohol. In 24 h after administration of ethanol-prednisolone mixture, rats were removed from the experiment. CEP was used in three modes of administration: prophylactic – 1 time per day for 5 days before the administration of ethanol-prednisolone mixture; therapeutic – once in 60 minutes after administration of ethanol-prednisolone mixture; therapeutic and prophylactic – 1 time per for 3 days before the administration of ethanol-prednisolone mixture and 60 minutes after the administration of ethanol-prednisolone mixture. The effect of the studied drugs on the condition of the gastric mucosa was assessed macroscopically on a scale Yakovleva L.V. Results. Macroscopic evaluation of the condition of the gastric mucosa showed that after 24 hours. after administration of the ethanol-prednisolone mixture, the degree of damage averaged 3.7±0.37 points out of the five maximum possible points, and the ulcer index was 3.9 units from prophylactic five-day administration of esomeprazole resulted in an antiulcer activity of 45.9%, which was 1.8 times lower than that of the CEP. Erosive-ulcerative lesions of the gastric mucosa on the background of treatment-and-prophylactic modes of CEP were observed in only 28.6% of rats, which corresponded to the value of the ulcer index (0.3 units), and antiulcer activity was 92.3%. Under this regimen, the antiulcer activity of the CEP was practically comparable to the severity of the indicated activity of esomeprazole (97.4%). Conclusions. The administration of CEP in the treatment mode (1 time after ethanol-prednisolone mixture) is accompanied by the lowest antiulcer activity, which was 22.2%, which was 4.1 times lower than the effectiveness of esomeprazole. Therapeutic and prophylactic use of CEP led to a statistically significant (p<0.05) attenuation of the damaging effects of ethanol-predniolone mixture, and antiulcer activity was 92.3%, respectively.
Koshurba I. V., Hladkykh F. V. Preclinical study of gastroprotective action of cryopreserved placenta extract. Abstracts of International scientific interdisciplinary conference «ISIC–2022»; 2022 November 17; Kharkiv, Kharkiv: Kharkiv National Medical University of the Ministry of Health of Ukraine. 2022. P. 88–89. DOI: https://doi.org/10.5281/zenodo.7404700.